Advance Care Planning and Shared Decision-Making: An Interprofessional Role-Playing Workshop for Medical and Nursing Students - Carl Grey; Lori Constantine; Gina M. Baugh; Elizabeth Lindenberger (Association of American Medical Colleges, 2017)
Introduction Advance care planning (ACP) is an essential discussion between a health care provider and a patient about their future care during serious illness. In clinical practice, high-quality ACP may be addressed with an interprofessional approach. Role-playing is an ideal method to practice both ACP and shared decision-making before having these conversations with patients. Methods This asynchronous role-playing workshop is prefaced with two prerecorded 25-minute videos for faculty and student preparation with one introducing ACP concepts, and one depicting a patient-physician ACP discussion. During the 2-hour workshop, students complete four role-play ACP scenarios with the following roles: patient, family member, nurse, nurse practitioner, and physician. Students rotate through different roles guided by scripts, and have a fact sheet for each scenario detailing prognostic information for disease processes. The role-play works optimally with three nursing students, three medical students, and one faculty facilitator per group. Facilitators are provided with a timeline, a guide for debriefing, and an evaluation rubric. Results The survey data from 85 students spread over four course offerings were summarized. When asked both if learning objectives were met, and to reflect on the clinical relevance, teaching effectiveness, and the overall workshop experience, most participants reported a good to excellent rating. Discussion This role-play activity allows students to practice ACP and shared decision-making, both with patient and family presence, and in premeeting rounds with the health care team. ACP exposure during student training helps trainees recognize the impact of high-quality interprofessional conversations on the care patients want and ultimately receive.